Transition metal supported UiO-67 materials and their applications in catalysis - Li, Tingting; Li, Yan; Mao, Jingxin (Frontiers in Chemistry, 2025)
Metal-organic frameworks (MOFs) have emerged as promising platforms for heterogeneous catalysis due to their tunable structures and high specific surface areas. Results indicate that modified composite MOFs not only exhibit superior water stability but also demonstrate broader applicability in catalysis, such as Fenton-like oxidation, Morita-Baylis-Hillman reactions, ethylene dimerization, and various photoelectrochemical processes. Among them, UiO-67, a zirconium-based MOF, has attracted extensive attention for its exceptional chemical stability, high catalytic activity, and well-defined microporous structure. This review introduces composites formed by different types of single and multi-metal loadings on UiO-67 and their demonstrated catalytic performance. It emphasizes the structure-performance relationships of these composites, highlighting how metal loading and spatial distribution influence their reactivity and stability. The current application status and existing challenges of UiO-67 series materials and their derivatives in catalysis are systematically reviewed. By integrating experimental results and mechanistic insights, this work underscores the transformative potential of UiO-67 series materials in meeting the demands of sustainable catalysis.